Persepsi Mahasiswa Akuntansi terhadap Pengetahuan Teknologi Informasi Akuntansi (Studi Kasus pada Mahasiswa Program Studi Akuntansi Universitas HKBP Nommensen) - Bawamenewi, Mei Masrohani; Siahaan, Audrey M.; Saribu, Ardin Dolok (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research aims to find out how different the perceptions of HKBP Nommensen University Accounting Students are regarding Knowledge of Accounting Information Technology based on their cumulative Achievement Index. The independent variable is the perception of accounting students, and the dependent variable is knowledge of information technology. The research method used is primary data collection techniques in the form of questionnaires.The sampling method used in this research was convenience sampling, with a sample size of 90 respondents. Data management uses SPSS version 25 tools. Tests used in this research include descriptive statistical analysis, validation and reliability tests, normality tests, and one way anova tests.Based on the research results, it shows that based on the one-way ANOVA test with a p-value of 0.040 with an alpha of 0.05, meaning that the probability value is greater than alpha, so Ho is accepted, it can be concluded that there is no difference in students' perceptions of accounting information technology knowledge based on grade-point average.